The Beluru Chennakeshava temple - Ishwar Phulari (2021)
The Chennakeshava temple is in the state of Karnataka in the town of Beluru. The many inscriptions carved on the walls of the temple and on standalone stones have well preserved the history of the Hoysala dynasty and the temple. The inscriptions call this town Velapura which has eventually become Beluru.